Rancang Bangun Lux Meter Real Time Berbasis Internet of Things - Indrawata Wardhana; Vandri Ahmad Isnaini; Rahmi Putri Wirman; Novitasari Novitasari; Ogie Indra Gunawan (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
Sunlight data intensity is highly required for Indonesia which is located in the line of the equator. This research builds a real-time sunlight intensity observation system based on the Internet of Things (IoT), in which the data can be easy to access everywhere. This tool is designed using microcontroller NodeMCU and LDR module which has been calibrated by Luxmeter Lx-103. Data is sending using Message Queuing Telemetry Transport protocol Quality of Service 1. The trial was carried out for 12 hours outside. Obtaining research results that linear regression LDR:  y = -2758.289*voltaseADC + 48.981 and = 0.9693, with sunlight intensity maximum that can be counted is 28 VADC, average range light intensity in middle daytime is 4 – 60 VADC. Production data by LDR was proceeded by NodeMCU then showed in LCD with a time delay one second. Data was sent to mqtt server with interval 60 seconds, last steps data stored in database SQLite.